The Effect of Project-Based Learning Model on Students’ Cognitive Learning Outcomes and Collaborative Skill of Excretion System Concept - Sulfahmi Mursalim; Nurdiyanti Nurdiyanti; Wira Yustika Rukman; Muhammad Wajdi (Jurnal Penelitian Pendidikan IPA, 2023)
This research is quasi-experiment research which aims to: 1) Knowing the effect of implementing Project Based Learning toward students' cognitive learning outcomes on the human excretory system material for class XI MIA at SMA Negeri 2 Pangkep. 2) Knowing the effect of implementing Project Based Learning on students' collaborative skills on the human excretory system material for class XI MIA at SMA Negeri 2 Pangkep. This research uses a Non-Equivalent Control Group Design. Samples in this study were class XI MIA Plato and XI MIA Alexander Graham Bell. Data collection techniques were used in the form of learning outcomes tests and collaborative skills questionnaires by conducting observations and documentation. The data were collected by giving a pretest and posttest, which were then analyzed through descriptive and inferential analysis. The hypothesis test using the N-Gain Independent Sample t-Test. The results of this study indicate that: 1) students' cognitive learning outcomes in the experiment class have an average score of 85.17, while the control class is 73.03. Based on the results of hypothesis testing, a significant value was obtained, namely 0.000 < = 0.05. 2) students' collaborative skills in the control class have an average score of 76.66%, while the control class is 59.33. Based on the results of hypothesis testing, a significant value was obtained, namely 0.000 < = 0.05. By looking at the results of hypothesis testing, Project Based Learning affects students' cognitive learning outcomes and collaborative skills of class XI at SMA Negeri 2 Pangkep